Knowledge gaps in understanding the metabolic and clinical effects of excess folates/folic acid: a summary, and perspectives, from an NIH workshop. Issue 5 (6th October 2020) - Maruvada, Padma; Stover, Patrick J; Mason, Joel B; Bailey, Regan L; Davis, Cindy D; Field, Martha S; Finnell, Richard H; Garza, Cutberto; Green, Ralph; Gueant, Jean-Louis; Jacques, Paul F; Klurfeld, David M; et al.
ABSTRACT: Folate, an essential nutrient found naturally in foods in a reduced form, is present in dietary supplements and fortified foods in an oxidized synthetic form (folic acid). There is widespread agreement that maintaining adequate folate status is critical to prevent diseases due to folate inadequacy (e.g., anemia, birth defects, and cancer). However, there are concerns of potential adverse effects of excess folic acid intake and/or elevated folate status, with the original concern focused on exacerbation of clinical effects of vitamin B-12 deficiency and its role in neurocognitive health. More recently, animal and observational studies have suggested potential adverse effects on cancer risk, birth outcomes, and other diseases. Observations indicating adverse effects from excess folic acid intake, elevated folate status, and unmetabolized folic acid (UMFA) remain inconclusive; the data do not provide the evidence needed to affect public health recommendations. Moreover, strong biological and mechanistic premises connecting elevated folic acid intake, UMFA, and/or high folate status to adverse health outcomes are lacking. However, the body of evidence on potential adverse health outcomes indicates the need for comprehensive research to clarify these issues and bridge knowledge gaps. Three key research questions encompass the additional research needed to establish whether high folic acid or total folate intake contributes to disease risk. 1 ) Does UMFA affect biological pathways leading to adverse health effects? 2 ) Does elevated folate status resulting from any form of folate intake affect vitamin B-12 function and its roles in sustaining health? 3 ) Does elevated folate intake, regardless of form, affect biological pathways leading to adverse health effects other than those linked to vitamin B-12 function? This article summarizes the proceedings of an August 2019 NIH expert workshop focused on addressing these research areas.